PENGARUH LATIHAN HOME BASE TERHADAP KETERAMPILAN DRIBBLE SSB PAUH DUO FC U-12 - Febramatul Ikbal; Zainur Zainur; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrack: The problem in this research is that the dribbling skills of SSB Pauh Duo FC U-12 players are still lacking, this can be seen in various trials and official competitions and this is one of the factors that cause defeat. This type of research is a kind of experimental research to see the effect of the form of training. The aim of this is to look at the effect of home base training on dribbling skills on Pauh Duo FC U-12 SSB players. The population in this research was the Pauh Duo FC U-12 team, with a total of 16 people. The sampling technique is to use the total sampling, whereby the total population is sampled. The instrument in this research used the dribble test as a tool to measure driblle skills. The data is then statistically processed to test the normality using the lilifours test at a significance level of 0.05 a. Based on the analysis of the normality of the data X, it produces an LoMax of 0.198 and an Ltable of 0.213, which means that the LoMax < Ltable. while the Y variable produces LoMax of 0.188 and Ltable of 0.213. This means LoMax < LTabel. Analysis was performed by t test. based on data analysis and conclusion, it can be concluded that there is a significant effect of home base training on the dribbling skills of Pauh Duo FC U-12 SS Solok Selatan players proven by Tcount of 6,285 and Ttable 1,753. Means Tcount> Ttable At the level of ɑ = 0.05.Key Words: Home Based Training, Dribbling Skills